In depth chemical investigation of Glycyrrhiza triphylla Fisch roots guided by a preliminary HPLC-ESIMSn profiling. (15th May 2018) - Shakeri, Abolfazl; Masullo, Milena; D'Urso, Gilda; Iranshahi, Mehrdad; Montoro, Paola; Pizza, Cosimo; Piacente, Sonia
Highlights: The roots of Glycyrrhiza tryphilla from Iran were investigated for the first time. The metabolite profile of the MeOH extract obtained by LC-ESI/LTQOrbitrap/MS highlighted the occurrence of 21 main compounds. Six compounds never reported before have been characterized by HR/MS and NMR analysis. Isolated compounds belong to isoflavone and saponin classes. Abstract: Chemical investigations on Glycyrrhiza spp. have mostly been focused on G. glabra (typically cultivated in Europe, henceforth called European licorice), G. uralensis and G. inflata (known as Chinese licorice) with little information on the constituents of other Glycyrrhiza species. According to the growing interest in further Glycyrrhiza spp. to be used as sweeteners, the roots of G. triphylla have been investigated. The LC-ESI/LTQOrbitrap/MS profile of the methanolic extract of G. triphylla roots guided the isolation of 21 compounds, of which the structures were elucidated by 1D- and 2D-NMR experiments. Based on this approach, 6 previously unreported compounds including two isoflavones 7, 5′-dihydroxy-6, 3′-dimethoxy-isoflavone-7- O -β-d -glucopyranoside (4 ) and 7, 5′-dihydroxy-6, 3′-dimethoxy-isoflavone-7- O -(7, 8-dihydro-p-hydroxycinnamoyl)-β-d -glucopyranoside (7 ) and four saponins, named licoricesaponins M3 (13 ), N2 (14 ), O2 (16 ) and P2 (18 ), have been characterized. It is to be noted that the accurate masses of some compounds here reported for the first time corresponded to those of compounds previously described in Glycyrrhiza spp. Thus an approach based only on MS analysis could be misleading; only isolation followed by NMR analysis allowed us to unambiguously assign the structures of these previously unreported compounds.